ANALISIS PENGARUH PERTUMBUHAN EKONOMI, UPAH MINIMUM DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP TINGKAT PENGANGGURAN DI PROVINSI JAWA TIMUR TAHUN 2008-2014 - Nurcholis, Muhammad (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2014)
In this study, the expected goal is to determine the distribution, classification and influence economic growth, minimum wage, and the Human Development Index of the level of unemployment in East Java Province 2008-2012. This research uses descriptive quantitative research methods. Data analysis in accordance with the formulation of the problem and the purpose of the study is using panel data regression analysis model and using the classification of the intensity and GIS. Based on panel data regression results show that perumbuhan economy, the minimum wage and the human development index have a significant effect on the unemployment rate. Variable economic growth and the negative effect of minimum wages, while the human development index positive effect. As for testing the F calculation, economic growth, the minimum wage and the human development index have a significant effect on the unemployment rate.